The Characteristics of CNT/Cement Composites with Acid-Treated MWCNTs - Su-Tae Kang; Jun-Yeong Seo; Sun-Hong Park (Advances in Materials Science and Engineering)
This study investigated the effects of acid-treated MWCNTs on the workability, compressive and tensile strength, porosity, and microstructure of CNT/cement composites. While workability decreased with acid treatment of CNTs, compressive and tensile strength improved significantly. Strength was also enhanced by using acid-treated CNTs alone, compared to using a surfactant with acid-treated CNTs. MIP analysis revealed that the porosity decreases from using acid-treated CNTs and that using acid-treated CNTs without a surfactant was more effective in reducing the size of micropores. A SEM analysis revealed improved CNT dispersion and dense hydration products in cement composites containing acid-treated CNTs. Ultimately, the use of acid-treated CNTs improved the CNT dispersion within CNT/cement composites, enhanced the pore structure, and formed denser hydration products around CNTs.